Effects of APOE e4-allele and mental work demands on cognitive decline in old age: Results from the German Study on Ageing, Cognition, and Dementia in primary care patients (AgeCoDe) - Rodriguez, Francisca S.; Röhr, Susanne; Pabst, Alexander; Kleineidam, Luca; Fuchs, Angela; Wiese, Birgitt; Lühmann, Dagmar; Brettschneider, Christian; Wolfsgruber, Steffen; Pentzek, Michael; Bussche, Hendrik van den; König, Hans-Helmut; et al. (International journal of geriatric psychiatry, 2021)
Objectives: Previous studies have observed protective effects of high mental demands at work on cognitive functioning and dementia risk. However, it is unclear what types of demands drive this effect and whether this effect is subject to a person's genetic risk. We investigated to what extent eight different types of mental demands at work together with the APOE e4 allele, a major risk gene for late-onset Alzheimer's disease, affect cognitive functioning in late life. Methods/Design: The population-based German Study on Ageing, Cognition, and Dementia in Primary Care Patients (AgeCoDe, n = 2 154) followed cognitively healthy individuals aged 75 years and older in seven assessment waves. Cognitive functioning was assessed via the mini-mental status examination. Results: Mixed-effects modeling (adjusted for education, gender, marital status, stroke, depression, and diabetes) indicated that participants who had an occupational history of working in jobs with high compared to low demands in “Language & Knowledge”, “Pattern detection”, “Information processing”, and “Service” had a slower cognitive decline. APOE e4-allele carriers had an accelerated cognitive decline, but this decline was significantly smaller if they had a medium compared to a low level of demands in contrast to non-carriers. Conclusions: Our longitudinal observations suggest that cognitive decline could be slowed by an intellectually enriched lifestyle even in risk gene carriers. Fostering intellectual engagement throughout the life-course could be a key prevention initiative to promote better cognitive health in old age.